(untitled) (Plant Tissue Culture and Biotechnology, 2016)
To investigate the influence of cultivar, medium, and explants on production of somatic embryogenic callus in grapevine (Vitis vinifera) an attempt was made. After callus production, calli were transferred into GS1CA medium for embryogenesis. In GS1CA medium, anther explant of Shahroodi cultivar showed the highest potential for production of embryogenic calli. Results showed that whole flower explants did not produce any embryogenic calli. In addition, leaf explants of Red?Sultanina and Flame Seedless were cultured on MS containing 1mg 2,4?D, 0.1 mg BA, 1 g/l casein hydrolisate, 20 g/l sucrose and 7 g/l agar were able to produce embryonic calli. After three months, calli were transferred to the MS with different concentrations of BA (1, 2 and 3.5 mg/l) and IAA (2, 5 and 15 mg/l). Results showed that among cultivars and different hormonal treatments, the medium containing 5 mg/l BA and 2 mg/l IAA induced maximum embryogenesis in Flame?Seedless calli. Plant Tissue Cult. & Biotech. 26(2): 219-230, 2016 (December)